Subwavelength metamaterial engineering for silicon photonics - Halir, Robert; Ortega-Moñux, Alejandro; Soler-Penades, Jordi; Luque-González, José Manuel; Sarmiento-Merenguel, Jose Darío; Sánchez-Postigo, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Schmid, Jens H.; Xu, Dan-Xia; Janz, Siegfried; Lapointe, J.; Molina-Fernández, Íñigo; et al. (My University, 2017)
Waveguides structured at the subwavelength scale frustrate di raction and behave as optical metamaterials with controllable refractive index. These structures have found widespread applications in silicon photonics, ranging from sub-decibel e ciency bre-chip couplers to spectrometers and polarization rotators. Here, we briefly describe the design foundations for sub-wavelength waveguide devices, both in terms of analytic e ective medium approximations, as well as through rigorous Floch-Bloquet mode simulation. We then focus on two novel structures that exemplify the use of subwavelength waveguides: mid-infrared waveguides and ultra-broadband beamsplitters.
Keywords: Fotónica; Guías de ondas; Silicon photonics; Subwavelength structures; Near infrared; Mid infrared; Ultra broadband devices